Studi Eksperimen Pengaruh Penggunaan Catalytic Converter Kuningan (Cu-Zn) Terhadap Torsi, Daya Dan Tekanan Efektif Rata-rata Motor Bensin Empat Langkah - Andi Sanata, (Teknika, 2007)
Low pollutant and high performance motorcycle has become a need in this time. The use of catalytic converter with brass content is aimed to reduce the pollutant gas of the motorcycle and also to raise its engine performance.This research test the influence of catalytic converter use to the engine performance, these are torsion, power and break mean effective pressure. Brass is placed in a muffler of a exhaust systems design with many varieties of brass mass, these are 80, 100, 120, 140, 160, 180 and 200 gr as a catalyst. The experiment is done by comparing the standard condition and the exhaust systems condition after using the catalytic converter, to the Honda Karisma 125 cc engine.From the result of this research, the use of brass catalytic converter can raise about 13,39 5 torsion, 16,87 % power and 13,39 % break mean effective pressure in optimum condition of 160 gr brass content.